Uganda Dairy Supply Chain Risk Assessment - World Bank (Washington, DC, 2017)
Cattle are one of the main instruments for economic (e.g., milk, meat, and cattle sale) and social (e.g., marriage, death, dispute settlement, and gift giving) exchange in Uganda. They serve as the main source of livelihood for a large majority of rural Ugandans, especially in the cattle corridor. Recent statistics demonstrate that the livestock sector contributes 13.1 percent of the agricultural gross domestic product (GDP) and 5 percent of the national GDP. Since 1991, the output of the livestock sector has grown on an average of 2.2 percent per annum, with most of the growth coming from the dairy sector. Dairy is an important and growing sector of Uganda's economy, and it is increasingly proving to be a lucrative livelihood option for a large number of households engaged in milk production and trade. Frequent realization of risks, however, impacts the performance of the supply chain. Effective management of these risks will require increased efforts to mitigate the identified risks and strengthen coping mechanisms. However, rather than a stand-alone risk management strategy, these efforts should be an integral component of a broader dairy development policy and strategy.